Engineered! : engineering design at work - Hunt, Shannon (Shannon Chantal) (Kids Can Press, 2017)
Presents an illustrated exploration of what it is like to be an engineer, discussing the steps of the engineering design process and then covering nine stories of real-world engineering ingenuity, as engineering problem-solvers send rovers to Mars and make computer circuits small enough to fit in the palm of one's hands.